2010
DOI: 10.1677/erc-10-0109
|View full text |Cite
|
Sign up to set email alerts
|

Expression of trophic amidated peptides and their receptors in benign and malignant pheochromocytomas: high expression of adrenomedullin RDC1 receptor and implication in tumoral cell survival

Abstract: Pheochromocytomas are catecholamine-producing tumors which are generally benign, but which can also present as or develop into malignancy. Molecular pathways of malignant transformation remain poorly understood. Pheochromocytomas express various trophic peptides which may influence tumoral cell behavior. Here, we investigated the expression of trophic amidated peptides, including pituitary adenylate cyclase-activating polypeptide (PACAP), neuropeptide Y (NPY), and adrenomedullin (AM), and their receptors in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…Membrane-associated CXCR7 is expressed on a number of tumor cell lines, activated endothelial cells and fetal liver cells, but is absent on other cell types (4). A receptor exhibited a four-fold higher expression in malignant pheochromocytomas compared with benign ones (5). Ectopic CXCR7 expression in NIH 3T3 cells significantly increased cell proliferation and formed tumors when xenografted in nude mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane-associated CXCR7 is expressed on a number of tumor cell lines, activated endothelial cells and fetal liver cells, but is absent on other cell types (4). A receptor exhibited a four-fold higher expression in malignant pheochromocytomas compared with benign ones (5). Ectopic CXCR7 expression in NIH 3T3 cells significantly increased cell proliferation and formed tumors when xenografted in nude mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CGRP receptor components and CGRP activity has been examined in several tumours and tumour-derived cell lines. For example, RAMP1 mRNA expression has been detected in benign and malignant pheochromocytomas (Thouennon et al 2010), Conn's adenoma (Forneris et al 2001) and pancreatic cancers (Ramachandran et al 2007).…”
Section: C5mentioning
confidence: 99%
“…In the original publication, it was reported that RDC1 could also bind AM with low affinity (200 nM). This seems to have generated the notion that RDC1 is a putative AM receptor (Thouennon et al 2010). There has been no independent verification that RDC1 can bind AM and until it can be demonstrated that RDC1 can produce a functional response inside a cell on binding AM, it cannot be considered as an AM receptor.…”
Section: L Hay Et Al: Am and Cgrp In Endocrine-related Cancersmentioning
confidence: 99%
See 2 more Smart Citations